Understanding turnover of generation Y early-career workers: The influence of values and field of study - Rueff-Lopes, R.; Velasco, F.; Sayeras, J.; Junça Silva, A. (Personnel Review, 2025)
Purpose Generation Y early-career workers have the highest turnover rates ever seen. To better understand this phenomenon, this study combines the P-O values fit with the Cohort perspectives to (1) identify the work-related values of this generation, (2) explore the relation between values and turnover intentions and examine how the field of study influences this relationship and (3) verify if the turnover intentions materialized one year after the first data collection. Design/methodology/approach We interviewed 71 early-career workers and applied thematic analysis to identify the value categories. A classification decision tree tested whether the field of study influences the relation between values and turnover intentions. A post-test was conducted to determine whether the reported turnover intentions were materialized one year later. Findings Thematic analysis yielded 285 themes that were grouped into 12 values’ categories. Decision trees revealed that the combination of values that most predicted turnover was substantially different between Finance graduates (more instrumental and future-oriented values) and Innovation and Entrepreneurship graduates (more social and job-oriented values). The post-test confirmed that the number of respondents who reported an intention to quit their jobs during the interview with us and did quit one year later was statistically significant. Originality/value To our knowledge, this is the first study that uses critical incident interviews to explore the work-related values of this specific cohort and their relation to turnover. Our findings on the moderating effects of the field of study are unprecedented. We also identified three new work-value categories, and, to our knowledge, this is the first study that used decision trees to explore the relation between values and turnover.